Advisory Boards in Medium-Sized Companies An International Comparison - Bruno, Sabrina; Ecker, Julius; Graewe, Daniel; Holthuis, Jan; Jiao, Li; Kaisarov, Ivan; Luke, Antje; Lux, Dietmar; Mukhin, Victor; Penna, Paulo; Ricci, Francesca; Shinzato, Luisa; et al. (De Gruyter, 2021)
Advisory boards offer various advantages in corporate settings related to shareholder relief, consulting know-how, and marketing. They have been gaining increasing importance across the world, especially in medium-sized companies which by nature differ from large corporations in their independent business models, leaner structures and special culture. With contributions from renowned practical experts from several countries, Advisory Boards in Medium-Sized Companies helps to classify, compare and understand the role of advisory boards in SMEs in the main legal and economic systems around the world. This useful and timely book analyses the legal structure and framework of advisory boards in different countries and provides an overview of their situation, furthering critical mutual understanding of corporate law at the international level. Experienced practitioners from each country have brought together their experiences to improve the understanding of, and raise awareness of the benefits of, advisory boards through up-to-date and practice-oriented country reports. This book provides valuable insights for managers, shareholders, consultants, practitioners and academics alike.